Designing a renewable energy harvesting park as an alternative energy source for the Aurora Province, Philippines - Tan, Jeffrey Steven K.; Fontanoza, Franklin Jr. S. (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
The ever-rising demand for energy has always resulted to excessive carbon emissions caused by burning fuels. The International Energy Agency (2021) has forecasted that electricity demand will rise by around 3-4 percent anually. This will mean that carbon emissions from producing energy will reach record levels this 2022. The continuous increase of carbon emissions creates a potential problem that the world may not be able to achieve the Paris Agreement in 2015. Despite the continuous rise of renewable energy production, the transition is not happening fast enough. Moreover, in the Philippines, the use of renewable energy as energy supply is barely keeping up with the additional demand of electricity. This research aims to create a renewable energy harvesting park in the province of Aurora in the Philippines. The renewable energy sources would be from solar, wind and wave energy.
This research has selected Baler, Aurora as the potential site for the wind, wave, and solar energy park. Through the proposed design it will be able to power Baler, Aurora until year 2035 by being able to produce at least 210MW of electrical energy daily. This energy park will lessen carbon emissions and create clean energy. This will be a pioneer in the country as there is no wind, wave, and solar energy harvesting parks in the Philippines. Once implemented it could help provide energy security for of a lot of Filipinos and at the same time be in line with the goals of World toward sustainable energy production.
includes appendices.
Thesis (Bachelor of Landscape Architecture)--University of the Philippines Diliman
Keywords: Energy parks -- Aurora (Baler); Greenhouses -- Aurora (Baler)